The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.14260/jemds/2014/2268
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cogulation Profile in Pre Eclamptic and Eclamptic Patients With Normotensive Pregnant Patients

Abstract: AIM: To compare the coagulation parameters in patients with preeclampsia and eclampsia with normotensive pregnant patients in Nainital district of Uttarakhand state. MATERIAL AND METHODS: From January 2012 to June 2013, coagulation indices including platelet count, prothrombin time (PT), activated partial thromboplastin time (aPTT), bleeding time (BT) and clotting time (CT) were measured in 100 patients with preeclampsia and eclampsia and compared with 100 normotensive pregnant women. The patients with coagulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
6
12
0
Order By: Relevance
“…Chauhan P found that in pre-eclampsia and eclampsia, decrease in platelet count (157.18±56.66 lacs/cumm) was highly significant (p<0.001). 8 This finding corroborated with this study.…”
Section: Platelet Countsupporting
confidence: 90%
“…Chauhan P found that in pre-eclampsia and eclampsia, decrease in platelet count (157.18±56.66 lacs/cumm) was highly significant (p<0.001). 8 This finding corroborated with this study.…”
Section: Platelet Countsupporting
confidence: 90%
“…Chauhan et al observed platelet count in cases as 157.18±56.66 x 10 9 /L and in controls as 222.93±97.94 x 10 9 /L. 20 Meshram DP observed platelet count 242±62 x10 9 /L in control group and 160±51 x10 9 /L in preeclampsia. 21 These authors also found significantly decreased platelet counts in pre eclampsia as compared to that in controls, similar to the present findings.…”
Section: Discussionmentioning
confidence: 95%
“…Alice Konijnenberg [21] observed that during preeclampsia there is a more extensively activated state of platelets while observing in Flow cytometric analysis when compared with normal pregnancy. Priyanka Chauhan et al [22] reported that platelet count decreased significantly among preeclampsia and eclampsia and PT, aPTT, CT were normal but BT was prolonged.…”
Section: Slmentioning
confidence: 99%